Energy Decay of Solutions to a Nondegenerate Wave Equation with a Fractional Boundary Control (Journal of Partial Differential Equations, 2021)
"In this paper, we study the energy decay rate for a one-dimensional nondegenerate wave equation under a fractional control applied at the boundary. We proved the polynomial decay result with an estimation of the decay rates. Our result is established using the frequency-domain method and Borichev-Tomilov theorem."
Keywords: Nondegenerate wave equation; fractional boundary control; Frequency domain method; Optimal polynomial stability.